Peningkatan Produksi Produk Menggunakan Lean Manufacturing System (Studi Kasus : UKM Mie Aceh Alya) - Toni Darji; Anita Susilawati; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Mie Aceh Alya is a small-scale house hold industry engaged in culinary making wet noodles. Process of making Aceh Alya’s noodles includes preparation of raw materials, mixing dough, printing and cutting, boiling, and cooling and packaging. To meet the demand of the product is often in overtime and delay of product delivery. The objectives of the research is to identification of waste occurring in the production process, to analyze the cause of the waste and to recommend the improvement on the production process, and to evaluate the quality of the product so that the productivity improvement can be achieved. The reseach conducted a case study in small scale industry i.e. Mie Aceh Alya. The research method used lean manufacturing system approach and Value Stream Mapping (VSM) method. Based on the calculation of the initial stage of the design can reduce lead time on the current production floor from 548,12 minutes to 438,95 minutes, so the company can produce more quickly and the delay of product delivery can be eliminated or reduced. Result of entification using WRM method was obtainad three biggest wastes that was defect of 14.86%, motion 14.61%, and prosess of 14.61%. The selection of detail mapping tools with Value Stream Analysis Tools (VALSAT) method was obtained the greatest value of PAM. From Process Activity Mapping (PAM) analysis obtained the was value added equal to 322,48 minutes or 58.83% from total time and 41.17% for non value added based improvement recommendation can decrease lead time at production floor of 1,82 hours.Keywords: Lean manufacturing system, VSM, Waste